Factors associated with blunt internal carotid artery injury in petrous temporal bone fractures. Issue 6 (June 2022) - Li, Christine; Green, Lorne; Wang, Jennifer; Tully, Dylan; Woliansky, Jonathan; Gumm, Kellie; Iseli, Claire; Martin, Katherine; Read, David
Highlights: Blunt ICA injuries tend to occur in patients with very severe head trauma Patients with PTB fractures involving the carotid canal or presenting with a GCS less than nine should be screened for ICA injury with a CTA scan Motor vehicle and motorbike crashes are more likely to result in blunt ICA injuries than other mechanisms Abstract: Introduction: Traumatic internal carotid artery (ICA) injuries are an uncommon complication of petrous temporal bone (PTB) fractures that can have devastating consequences of stroke, haemorrhage and death. Current guidelines suggest that all PTB fractures should be screened for blunt cerebrovascular injury, however clinical practice varies. The purpose of this study was to identify features associated with PTB fractures that increase the likelihood of ICA injury. Methods: A retrospective cohort study was performed on all patients with PTB fractures who were investigated with computed-tomography angiography (CTA) scan admitted to a Level One Trauma Service in Melbourne, Australia from 2015-2020. Patient demographic and injury data were obtained from The Royal Melbourne Hospital Trauma Registry and medical records. Multivariate binomial logistic regression was performed to identify features associated with ICA injury. Results: Out of 377 patients with 419 PTB fractures, 205 received a CTA scan and were included, identifying 22 ICA injuries (9.4%). The median age of ICA injuries was 33 (IQR 23-61), median Abbreviated Injury Scale (AIS) score for the head region was 5 (IQR 5-5) and the in-hospital mortality rate was 45.5%, mainly due to unsurvivable brain injury. Five patients (22.7%) developed ICA-specific complications of stroke or carotid-cavernous fistula. We identified five factors that were significantly associated with ICA injury. These included PTB fractures involving the carotid canal (OR 6.7, 95% CI 1.9–23.9, p=0.003), presenting with an initial GCS less than nine (OR 5.7, 95% CI 1.2-26.5, p=0.025) and increasing head AIS (OR 2.4, 95% CI 1.2-4.6, p=0.009). Mechanisms of injury that were associated with ICA injury were motor vehicle crash (OR 4.4, 95% CI 1.4-14.2, p=0.012) and motorbike crash (OR 4.6, 95% CI 1.2-18, p=0.029). Conclusion: Patients with PTB fractures and an additional feature of carotid canal involvement, presenting GCS less than nine, increasing head AIS indicative of severe head trauma or mechanism of injury by motor vehicle or motorbike crash, are at an increased risk of ICA injury and should be screened with a CTA scan.